A new species and an additional record of the genus Dilobitarsus Latreille (Coleoptera, Elateridae, Agrypninae) from Borneo - Arimoto, Kôichi; Kaliang, Clement Het; Mizuno, Takafumi; Meleng, Paulus; Kishimoto-Yamada, Keiko; Itioka, Takao (Zootaxa, 2025)
Elaterid beetles of the genus Dilobitarsus Latreille, 1834 (tribe Agrypnini Candèze, 1857; subfamily Agrypninae Candèze, 1857) are predominantly found in the New World. However, one species, Dilobitarsus pendleburyi Fleutiaux, 1934, lives in Southeast Asia. Determining the systematic position and taxonomic relationships among congeners remains challenging due to their isolated distribution in Asia. This study examined new specimens from Borneo, including a newly discovered species, D. lambirensis sp. nov., and discusses the morphological features of Southeast Asian species. The two Asian species are considered the most similar within the genus by sharing specific features.